2014
DOI: 10.1007/s13361-014-0855-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Metal–Peptide Complexation on Fragmentation and Inter-Fragment Hydrogen Migration in Electron Transfer Dissociation

Abstract: The use of metal salts in electrospray ionization (ESI) of peptides increases the charge state of peptide ions, facilitating electron transfer dissociation (ETD) in tandem mass spectrometry. In the present study, K(+) and Ca(2+) were used as charge carriers to form multiply-charged metal-peptide complexes. ETD of the potassium- or calcium-peptide complex was initiated by transfer of an electron to a proton remote from the metal cation, and a c'-z• fragment complex, in which the c' and z• fragments were linked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 30 publications
0
30
0
Order By: Relevance
“…Sequence information from the resulting metallated peptide cations has been obtained in studies employing ECD [57][58][59][60][61][62][63][64][65][66][67][68] and ETD. [69][70][71][72] Flick and Williams [68] demonstrated the ability of trivalent lanthanide metal ions to produce multiply positively charged ions with peptides. During a recent ETD study [72] involving the addition of trivalent lanthanide metal cations to acidic peptides, we also noted that multiply charged metallated ions form by ESI even in the absence of a highly basic arginine amino acid residue (gas-phase basicity of arginine = 1006.6 kJ/mol [73] ).…”
Section: Introductionmentioning
confidence: 99%
“…Sequence information from the resulting metallated peptide cations has been obtained in studies employing ECD [57][58][59][60][61][62][63][64][65][66][67][68] and ETD. [69][70][71][72] Flick and Williams [68] demonstrated the ability of trivalent lanthanide metal ions to produce multiply positively charged ions with peptides. During a recent ETD study [72] involving the addition of trivalent lanthanide metal cations to acidic peptides, we also noted that multiply charged metallated ions form by ESI even in the absence of a highly basic arginine amino acid residue (gas-phase basicity of arginine = 1006.6 kJ/mol [73] ).…”
Section: Introductionmentioning
confidence: 99%
“…Dong and Vachet [51] performed ETD on small copper-cationized peptides and observed c- and z-ions. For several acidic peptides, Asakawa and coworkers [52] demonstrated that metallated peptide ions with 2+ or 3+ charges produced by cationization with potassium or calcium ions underwent more sequence-informative ETD as compared to dissociation of the analogous protonated ions. In another study, Asakawa and Wada [53] complexed peptides containing cysteine residues with three divalent metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of a protonated precursor, metal-peptide complexes give a c'/z• fragment pair by ECD/ETD for most metal cations [13][14][15][16][17][18][19], suggesting that the fragmentation proceed via Utah-Washington model. In contrast, transition metal cations with a partially filled d orbital shell, such as Co 2+ , Ni 2+ , and Cu 2+ , are reduced by ECD/ETD [15,20].…”
Section: Introductionmentioning
confidence: 99%